A Jasmonate-Inducible Defense Trait Transferred from Wild into Cultivated Tomato Establishes Increased Whitefly Resistance and Reduced Viral Disease Incidence - Escobar-Bravo, Rocío; Alba, Juan M.; Pons, Clara; Granell, Antonio; Kant, Merijn R.; Moriones, Enrique; Fernández-Muñoz, Rafael (Frontiers in Plant Science, 2016)
Whiteflies damage tomatoes mostly via the viruses they transmit. Cultivated tomatoes lack many of the resistances of their wild relatives. In order to increase protection to its major pest, the whitefly Bemisia tabaci and its transmitted Tomato Yellow Leaf Curl Virus (TYLCV), we introgressed a trichome-based resistance trait from the wild tomato Solanum pimpinellifolium into cultivated tomato, S. lycopersicum. The tomato backcross line BC5S2 contains acylsucrose-producing type-IV trichomes, unlike cultivated tomatoes, and exhibits increased, yet limited protection to whiteflies at early development stages. Treatment of young plants with methyl jasmonate (MeJA) resulted in a 60% increase in type-IV trichome density, acylsucrose production, and enhanced resistance to whiteflies, leading to 50% decrease in the virus disease incidence compared to cultivated tomato. Using transcriptomics, metabolite analysis and insect bioassays we established the basis of this inducible resistance. We found that MeJA activated the expression of the genes involved in the biosynthesis of the defensive acylsugars in young BC5S2 plants leading to enhanced chemical defenses in their acquired type-IV trichomes. Our results show that not only constitutive but also these inducible defenses can be transferred from wild into cultivated crops to aid sustainable protection, suggesting that conventional breeding strategies provide a feasible alternative to increase pest resistance in tomato.